Aurora borealis and string of pearls in vitreoretinal lymphoma: patterns of vitreous haze. Issue 11 (1st February 2019) - Marchese, Alessandro; Miserocchi, Elisabetta; Giuffrè, Chiara; Cicinelli, Maria Vittoria; Querques, Giuseppe; Bandello, Francesco; Modorati, Giulio
Abstract : Aims: Peculiar retinal signs of vitreoretinal lymphoma (VRL) have been identified. However, limited information on the vitreous features of VRL is available. This study aims to characterise the vitreous involvement in VRL with the help of multimodal imaging. Methods: In this retrospective, observational study, we reviewed charts and imaging of all patients with biopsy-proven VRL seen from January 2016 to April 2018 at a single referral centre. These included ultrawide-field imaging, ophthalmic ultrasonography and slit-lamp photography. The main outcome measures were patterns of vitreous haze of VRL, as observed by combining clinical and multimodal imaging information. Results: Twenty-six eyes of 13 patients were included. At presentation, vitreous haze was present in 24 eyes (92%) and was the only sign of VRL in 4 eyes (15%). Three patterns of vitreous haze were identified in VRL. An aurora borealis pattern was present in 12 eyes and showed linear opacities with a myriad of cells aligned along the vitreous fibrils. A string of pearls pattern was present in two eyes at baseline and developed in other four eyes after vitrectomy, showing fine fibrils connecting bunches of inflammatory material. A non-specific pattern was observed in 10 eyes. Ophthalmic ultrasound showed corpuscular material correlating with the grading of vitreous haze. Conclusion: VRL shows different patterns of vitreous haze. Multimodal imaging, including ultrawide-field imaging and slit-lamp photography, helps in recognising these patterns, raising suspicion for VRL.